1959
DOI: 10.3133/pp317c
|View full text |Cite
|
Sign up to set email alerts
|

Geology of Isla Mona Puerto Rico, and notes on age of Mona Passage

Abstract: Isla Mona and the nearby rock of Monito are situated in Mona Passage, about midway between Puerto Rico and the Dominican Republic. Isla Mona has an area of about 21 square miles and Monito less than a quarter of a square mile. Isla Mona is a limestone tableland, bounded by steep to vertical cliffs and fringed about its southern perimeter by a narrow low-lying coastal terrace. The climate of the island is semiarid; its mean annual rainfall is 88.1 inches. The flora is zerophytic and consists mostly of cactus, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Using the North Coast basin of Puerto Rico (Briggs, 1961) (Kaye, 1959;Briggs and Seiders, 1972;Gonzalez et al, 1997). These limestones and dolomites do not correlate compositionally with the units of northern and southern Puerto Rico and are likely the result of localized reef build up (Ruiz, 1993).…”
Section: Morphology and Geologymentioning
confidence: 99%
“…Using the North Coast basin of Puerto Rico (Briggs, 1961) (Kaye, 1959;Briggs and Seiders, 1972;Gonzalez et al, 1997). These limestones and dolomites do not correlate compositionally with the units of northern and southern Puerto Rico and are likely the result of localized reef build up (Ruiz, 1993).…”
Section: Morphology and Geologymentioning
confidence: 99%
“…A detailed description of the coastal geomorphology of Mona Island appears in Kaye (1959), Hernández-Ávila (1970), Briggs & Seiders (1972), Taggart (1992), and González et al (1997), the ora of the coastal plain was reported on by Woodbury et al (1977), and this vegetation was studied ecologically by Cintrón & Rogers (1991). The methodology used for this study follows Wiewandt (1975), and basically consisted in the observation and registration by means of photography and videos of the migration of C. clypeatus.…”
Section: Methodsmentioning
confidence: 96%
“…The geology of the island of Puerto Rico was based on the map compilation by Krushensky and Schellekens (1999), supplemented by mapping for Isla de Mona by Kaye (1959); the geology of Isla de Culebra was from mapping by Banks (1962); and the geology of Isla de Vieques was from mapping by Learned and others (1973).…”
Section: Tvsmentioning
confidence: 99%
“…In the U.S. Virgin Islands, Donnelly (1966) was the source of mapping for Saint John and Saint Croix, and Rankin (2002) was for Saint Thomas. Helsley (1960) was the primary source of mapping for the British Virgin Islands, with the exception of Anegada Island, whose geology was inferred from information in Kaye (1959).…”
Section: Tvsmentioning
confidence: 99%